Structural Characterization of a New Collagen Biomimetic Octapeptide with Nanoscale Self‐Assembly Potential: Experimental and Theoretical Approaches. Issue 2 (1st February 2022) - Mocanu, Cosmin Stefan; Petre, Brindusa Alina; Darie‐Ion, Laura; Drochioiu, Gabi; Niculaua, Marius; Stoica, Iuliana; Homocianu, Mihaela; Nita, Loredana Elena; Gradinaru, Vasile Robert
Abstract: Bioinspired peptides are attractive biomolecules which can improve our understanding of self‐assembly processes for rational design of new peptide‐based materials. Herein, a new amidated peptide FRSAPFIE (FRS), based on a sequence present in human collagen, was synthesized, characterized by mass spectrometry and subjected to self‐assembling investigations. The optimal conditions for self‐assembly were disclosed by dynamic light scattering at 32 °C and a peptide concentration of 0.51 %. In addition, AFM studies revealed ellipsoidal FRS shapes with an area between 0.8 and 3.1 μm 2 . The ability of self‐assembly was also proved using FAD dye as extrinsic fluorescence reporter. According to the theoretical analysis, the FRS peptide tends to form a bundle‐type association, with a type of fibrillary tangles particle. Altogether, our findings address new challenges regarding the FRS peptide which can be used in further self‐assembly studies to design biocompatible drug‐delivery platforms. Abstract : The design of new bioinspired materials is a topic that generates a great deal of interest and research. In this work, an amidated octapeptide (H2 N‐FRSAPFIE‐CONH2 ), derived from human collagen, was obtained by solid phase synthesis and further analyzed by spectroscopic, spectrometric, imagistic and theoretical approaches. The peptide displayed interesting self‐assembly features demonstrated by fluorescence, atomic force microscopy or dynamic light scattering. All these investigations revealed that this peptide could act as a template for novel nanomaterials.